A novel banded structure ceramic phosphor for high-power white LEDs. Issue 50 (9th June 2017) - Zhang, Ji-Yun; Luo, Zhao-Hua; Jiang, Hao-Chuan; Jiang, Jun; Chen, Chun-Hua; Zhang, Jing-Xian; Gui, Zhen-Zhen
Abstract : We report a novel ceramic phosphor with a banded structure, which consists of two components (with yellow and red light emissions, respectively) arranged alternately on the parallel surface of an LED chip. Abstract : A novel banded structure ceramic phosphor has been fabricated in this research. This structure provides a convenient and effective method for regulating the full spectrum. It has the advantage of being able to adjust the intensity of all three primary colors independently, regardless of the mutual absorption among different active ions.